“De piloso fonte sum”: On Dishonorable Backgrounds, Lawsuits, Guilds, and Artisans in Early Renaissance Cluj - FIREA, Ciprian (Studia Universitatis Babeș-Bolyai Historia Artium, 2023)
“De piloso fonte sum”: On Dishonorable Backgrounds, Lawsuits, Guilds, and Artisans in Early Renaissance Cluj. This study, based on an exceptional source (a judicial record of 1549, published here for the first time) aims at the restitution of the biography and the distinctive character and personality of Gregorius Pictor, an early Renaissance painter from Transylvania, while making recurrent references to the artistic milieu of the sixteenth century Cluj – the town where he was mainly active. The study reveals, undoubtedly, one of the most comprehensive painters’ biographies of Transylvania in early modern times.